Pengembangan Video Pembelajaran Animasi Fisika Berbasis Powtoon Pada Materi Pemanasan Global - Ricky Yoshua; Indica Yona Okyranida; Dandan Luhur Saraswati (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This research aims to develop and find out the feasibility of learning media in the form of the development of Powtoon-based physics animation animation videos on Global Warming Materials. This research uses R&D (Research and Development) research and development methods. But researchers only use 3 stages, namely Define, Design, Development. Researchers do not use dessimanation because this video is not to be disseminated but only learning methods in the classroom. The results of this product development are expected to facilitate teachers and learners in learning. In this product, validation tests are carried out by material experts, media experts, and linguists. The results of the scores obtained in the Powtoon-based physics learning animation video feasibility test on global warming materials from media experts obtained an average score of 78.66%. then the material expert obtained an average score of 85.00% then the assessment was obtained from the linguist with an average score of 81.00%, so that if the average of all validators obtained a score of 81.55%. It can be inferred from the percentage of average score results by material and media experts classified as